Socialization and Counseling About Health Traditional/Complementary Alternative Medicine for Mothers Pregnant - Alfian, RM; Rosyita, Hafna; Hernayanti, Hernayanti; Koniasari, Koniasari; Winda Amalia, Anindini; Sari Handayani, Dwi Ratna (Jurnal Health Sains, 2024)
Introduction: Health traditional / CAM (Complementary and Alternative Medicine) has Lots of Mothers interested in pregnant to overcome several complaints and objections to comfort during pregnancy. Besides they feel worried about consuming therapy However attention exists several side effects requires enough information Objective:  Know description effort counseling about health traditional or CAM to Mother Pregnant Method: studies literature about counseling /educational use of Health traditional or CAM for Mothers pregnant. Library data collection, or object research his research dug through diverse information bibliography. Using secondary data, via several related articles with health traditional /CAM. The analysis uses an annotation bibliography, which can be interpreted as a list of sources used in something study given a conclusion related to what is written in it Results: Review from the article as many as 5 and with the essence society uses a type of health method traditional / CAM to avoid the effect of side treatment Because the public considers treatment traditional/complementary relatively safer. There are many types of methods during pregnancy medicines and herbal plants. However, it means without risk rise, a pregnant must have competent knowledge about the utilization of therapy safe complement during pregnancy That reason CAM is used because CAM is easily obtained and cheaper costs. Conclusion: Socialization and Counseling health traditional /CAM required concerning utility type/modality Health Traditional /CAM safety or side effect necessary attention and condition Mother pregnant That Alone. Counseling involves husband, family, and energy health and midwives at the Community Health Center. Furthermore, more exploration carries on about the perception and meaning use health traditional. Next expected can increase synergy between service health conventional and health traditional/CAM.